Metabolic modeling of single bronchoalveolar macrophages reveals regulators of hyperinflammation in COVID-19 - Zhao, Qiuchen; Yu, Zhenyang; Zhang, Shengyuan; Shen, Xu-Rui; Yang, Hao; Xu, Yangyang; Liu, Yang; Yang, Lin; Zhang, Qing; Chen, Jiaqi; Lu, Mengmeng; Luo, Fei; et al. (iScience, 2022)
SARS-CoV-2 infection induces imbalanced immune response such as hyperinflammation in patients with severe COVID-19. Here, we studied the immunometabolic regulatory mechanisms for the pathogenesis of COVID-19. We depicted the metabolic landscape of immune cells, especially macrophages, from bronchoalveolar lavage fluid of patients with COVID-19 at single-cell level. We found that most metabolic processes were upregulated in macrophages from lungs of patients with mild COVID-19 compared to cells from healthy controls, whereas macrophages from severe COVID-19 showed downregulation of most of the core metabolic pathways including glutamate metabolism, fatty acid oxidation, citrate cycle, and oxidative phosphorylation, and upregulation of a few pathways such as glycolysis. Rewiring cellular metabolism by amino acid supplementation, glycolysis inhibition, or PPARγ stimulation reduces inflammation in macrophages stimulated with SARS-CoV-2. Altogether, this study demonstrates that metabolic imbalance of bronchoalveolar macrophages may contribute to hyperinflammation in patients with severe COVID-19 and provides insights into treating COVID-19 by immunometabolic modulation. [Display omitted] •Dysregulated metabolic activities of lung immune cells in severe COVID-19•Unbalanced metabolic reprogramming may lead to dysfunction of lung macrophages•Remodeling metabolism reduces inflammation in macrophages stimulated with SARS-CoV-2 Biological sciences; Immunology; Virology; Bioinformatics